PERAN DAN KONTRIBUSI GURU PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMKN 1 BARUMUN - Wardian Syah Nst; Zainal Efendi Hasibuan; Murtadha (Yayasan Baitul Hikmah al-Zain, 2024)
Driving teachers are learning leaders who are expected to be agents of change in student-centered education, by developing their potential holistically according to their learning needs. After going through education, driving teachers are expected to be able to implement their competencies through real action. However, there are indications that driving teachers only carry out concrete actions to fulfill the educational requirements for driving teachers. Therefore, researchers raised this issue to get an idea of ​​the role and contribution of driving teachers in their competence as driving teachers in implementing the implementation of independent learning at SMKN 1 Barumun. This research aims to describe how the competency of driving teachers is implemented in implementing independent learning at SMKN 1 Barumun. The research method used is a qualitative approach with a case study type of research. The objects discussed in this research are school principals and driving teachers. Data was collected through observation and interview techniques. The research results show that there are four roles of driving teachers in curriculum implementation. The four roles include: first, the driving teacher acts as a change agent; second, the driving teacher facilitates other teachers as creators of discussion and collaboration forums; third, the driving teacher acts as a motivator; and fourth, the driving teacher ensures a pleasant learning atmosphere. In conclusion, the driving teacher has implemented his competence in implementing independent learning, although consistency is still needed in its implementation.